Multiplicity of hereditary thrombophilic factors inherited from both parents results in child catastrophe - Afaf Hemeda (SpringerOpen, 2019)
Here we present a rare case of hereditary thrombophilia due to transfer of multiple hereditary thrombophilic factors from father and mother with lethal outcome.